2003
DOI: 10.3732/ajb.90.12.1777
|View full text |Cite
|
Sign up to set email alerts
|

Polarity of peatmoss (Sphagnum) evolution: who says bryophytes have no roots?

Abstract: The class Sphagnopsida (Bryophyta) includes two genera: Ambuchanania and Sphagnum. Ambuchanania contains just one rare species known from two Tasmanian localities, but Sphagnum comprises a speciose clade of mosses that dominates many wetland ecosystems, especially in the boreal zone of the Northern Hemisphere. Recent phylogenetic analyses have resolved well-supported clades within Sphagnum, but polarizing Sphagnum evolution has been problematic because the genus is so isolated that it is difficult to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 37 publications
0
102
1
1
Order By: Relevance
“…For instance, mosses are important contributors to bog formation and carbon trapping (Jones et al 1994;Shaw et al 2003) in peat lands, where almost 100 % of the ground layer is covered by mosses (Vitt and Wieder 2009) such as Sphagnum species. The relevance of biotechnology approaches regarding the production and cultivation of peat mosses is increasing due to the rising demand of peat as, e.g., substrate for horticulture (Beike et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, mosses are important contributors to bog formation and carbon trapping (Jones et al 1994;Shaw et al 2003) in peat lands, where almost 100 % of the ground layer is covered by mosses (Vitt and Wieder 2009) such as Sphagnum species. The relevance of biotechnology approaches regarding the production and cultivation of peat mosses is increasing due to the rising demand of peat as, e.g., substrate for horticulture (Beike et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…(Lindberg 1880: 25) Warnstorf (1900, Alaska (Photo: Blanka Shaw). Sphagnum comprises a speciose clade of mosses that dominates many wetland ecosystems, especially in the boreal zone of the Northern Hemisphere (Shaw et al 2003). In particular, Sphagnum is an important and conspicuous component in peatlands, which perform a significant global function in regulating the Earth's atmospheric chemistry as well as providing valuable economic commodities (Rochefort 2000).…”
Section: Figure 2 Leiosporoceros Dussiimentioning
confidence: 99%
“…As for PCR-RFLP, a technique already applied in mosses (Vanderpoorten et al, 2003), several nuclear and plastid DNA regions (ITS, PsbC-TrnS and TrnF-V1) were tested by a set of 17 restriction enzymes before the anonymous regions RAPDa, RAPDb and RAPDf (Shaw et al, 2003), but no polymorphism was found. The double digestion of RAPDf with HinfI -HindIII derived in a characteristic, reproducible band pattern for the clone (Fig.…”
Section: Moss Clone Molecular Characterizationmentioning
confidence: 99%
“…The anonymous DNA region RAPDf was amplified using the F-F and F-R primers and following the protocol reported in Shaw et al (2003). The PCR products were purified by GFX PCR DNA and Gel Band Purification Kit (Amersham Biosciences) and digested by a set of 17 restriction enzymes (Fermentas, Thermo Fisher Scientific) according to manufacturer's instructions.…”
Section: Pcr-rflpmentioning
confidence: 99%